Investigating the hydrostatic and hydrodynamic behaviour of large size butterfly valves using experimental and numerical methods - Aziz Shokuhi; Farid Vakili-Tahami; Mohammad Zehsaz; Akbar Shokuhi (مجله مدل سازی در مهندسی, 2015)
In this paper, c. For this purpose, stress distribution and deformation of the major parts of the valve and also, the hydrodynamic torque, which is applied to the valve-disk, have been calculated at different opening angles of the disk. To carry out the numerical analysis, coupled Computational Fluid Dynamics (CFD) and Finite Element based solid mechanics solution methods have been used. To validate the numerical results, the displacements of some critical points on the valve-disk have been measured and the results are compared with those obtained using numerical solution. Also, the hydrodynamic torque of a model valve has been measured using an experimental rig and the data are compared with the numerical results. Both comparisons show good agreement and approve the accuracy of the numerical solution method. The results show that maximum stress occurs at the valve shaft when it is fully closed and, hydrodynamic torque exerted on the disk becomes maximum when the valve is at almost fully open angle. The effect of different parameters such as disk-off set, flow direction and shape of the valve-disk on the hydrodynamic torque of the valve has been investigated. In this process, a modeling method to study the hydro dynamic behaviour of large size butterfly valves has been developed which can be implemented in other case studies by the manufacturers.